Pengaruh Motivasi Terhadap Kinierja Melalui Disiplin Kerja pada Pegawai Negeri Sipil (Jurnal Ekonomi dan Manajemen, 2025)
This study analyzes the effect of motivation on employee performance, with work discipline as a mediating variable, among Civil Servants at RSUD Waluyo Jati Kraksaan, Probolinggo Regency. Using a quantitative method with path analysis, data were collected through questionnaires from 100 respondents. The results indicate that motivation has a significant effect on work discipline (β = 0.532; p < 0.05) and employee performance (β = 0.468; p < 0.05). Work discipline also significantly influences employee performance (β = 0.412; p < 0.05). Furthermore, motivation has an indirect significant effect on performance through work discipline, with a mediation influence value of 0.219. The R² value of 0.635 indicates that 63.5% of the variability in employee performance can be explained by motivation and work discipline. The study concludes that increasing motivation and work discipline contributes to improving employee performance. Therefore, institutions should provide incentives to enhance motivation and implement clear discipline policies. Future research is recommended to consider other influencing factors, such as work environment and leadership style, for a more comprehensive understanding.